Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $u$ be a real-valued harmonic function in the plane. We know that $u$ satisfies the mean value property in the following form: for all $r$ > $0$

(i) $$ u(z_o) = \frac{1}{2\pi}\int_{0}^{2pi}u(z_o + re^{i\theta})d\theta $$

The question asks us to use the above formula to deduce the following identities for all $r$ > $0$


$$ u(z_o) = \frac{1}{2\pi r}\int_{_dD(z_o, r)} u(x,y)ds $$


$$ u(z_o) = \frac{1}{\pi r^2}\int\int_{_D(z_o, r)} u(x,y)dxdy $$

where $D(z_o, r)$ = {$z\in\mathbb{C}: |z-z_o| < r$}

Thoughts so far: The identities seem relatively straight forward, but I'm having a hard time deducing them from (i). I know $z = z_o + re^{i\theta}$ is a parametrization of the circle of radius $r$ centered at $z_o$. In class we showed that if we use this parametrization in Cauchy's Integral Formula, then we obtain (i), so it doesn't make sense to me to substitute $z$ back into (1). I'm not sure where to start really.

Sorry if the solution turns out to be very simple. It seems to me it should be and i'm probably missing something obvious.

share|cite|improve this question
sorry, i know it's not much to work with – matt Oct 21 '12 at 1:10
here's another shot at it: if we substitute $z = z_o + re^{i\theta}$ into (i), then $dz = rie^{i\theta}d\theta = rzd\theta$. we know $s = r\theta$, so $ds = rd\theta$.So, we have $u(z_o) = \frac{1}{2\pi r}\int_{_dD(z_o,r)}u(z)ds$. And substituting $u(z) = u(x + iy) = u(x,y)$ gives us (ii). – matt Oct 21 '12 at 2:23
for (iii) I have been trying to use Green's theorem, but so far I haven't worked it out correctly. – matt Oct 21 '12 at 2:26
up vote 1 down vote accepted

For part ii) substiute $z = z_o + re^{i\theta}$ and rewrite $d\theta = \frac{ds}{r}$ (since $s = r\theta$).


$$ u(z_o) = \frac{1}{2\pi r}\int_{_dD(z_o, r)} u(x,y)ds $$

Since $u(z) = u(x + iy) = u(x,y)$.

For part iii) rewrite:

$$ \int\int_{_D(z_o, r)} u(x,y) = \int_0^r (\int_{_dD(z_o, \rho)} u(x,y)ds)d\rho $$

By part i) the inner on the right hand side evaluates to $2\pi \rho u(z_o)$, so we have:

$$ 2\pi u(z_o) \int_0^r \rho d\rho = \pi r^2 u(z_o) $$


$$ u(z_o) = \frac{1}{\pi r^2}\int\int_{_D(z_o, r)} u(x,y)dxdy $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.